Propriedades físico-químicas e efeito prebiótico de pectina hidrolisada obtida de resíduos agroindustriais - Moura, Fernanda Aline de (2016)
Pectin is a soluble dietary fiber that in addition to its role in the food industry as a thickener and emulsifier, provides metabolic effects related to weight control, lipids and glucose levels. It is found in significant amounts in agro-industrial residues such as bark and fruit cake. Soybean hulls, a product derived from the bran extraction and legume oil, also has a large amount of pectin in its composition. However, sources of different characteristics tend to provide pectins with monomeric organization and differentiated properties, which determine its technological application and metabolic role. Moreover, studies have indicated that the products of its hydrolysis, in particular pectic oligosaccharides have bifidogenic characteristics are considered as a new class of prebiotics. However, changes in physical and chemical properties caused by hydrolysis and its metabolic effects are not well studied. The optimal amounts of pectic prebiotics consumption also require further evidence to be established. Therefore, the aim of this study was to select promising raw material for efficient extraction and hydrolysis of pectin, evaluating the resulting product (partially hydrolyzed pectin) and the physical and chemical properties and prebiotic potential in vivo. The agro-industrial waste used were soybean hulls, passion fruit peel and orange peel. The passion fruit peel was the raw material with the greatest potential for pectin extraction by presenting yield ( 15.71 %) and galacturonic acid content ( 51.3 % ) , similar to orange peel ( 17.96 % yield and 60.45 % of galacturonic acid) in pectic concentrate, but with residual levels of protein and lipids reduced. Although high pectin content in its composition , the yield of extraction of the polysaccharide was only 5.66 % for soybean hulls . Therefore, passion fruit peel was chosen for pectit prebiotics production. Acid hydrolysis was efficient for two hours to produce changes in molecular weight distribution profile of passion fruit peel pectin, increasing the amount of low molecular weight compounds. The physico-chemical properties form also altered by hydrolysis, with decreased water holding capacity and the copper connection, and increased capacity for absorbing fat. The addition of 0.25% of partially hydrolyzed passion fruit peel pectin provided prebiotic effect, resulting in increased production of short chain fatty acids in growth in rat cecum.